The Urgency of Digitizing Learning for Madrasah Aliyah Islamic Boarding School Students in The Era Of Society 5.0 - Radjak, Dwi Setiawati; Jusuf, Syarifudin; Bongkan, Andi Darmawan (LPPM Universitas Terbuka, 2024)
Digitized learning in Islamic boarding schools is an opportunity and, at the same time, the challenge of continuing to transform to make the learning process massively more efficient and comprehensive in every aspect of human life. In the current era of disruption, technological and industrial change is facing a significant revolution and is known as the Society 5.0 era. Of course, in facing the era of society 5.0, the world of education has an important contribution to make in adapting to current developments in improving the quality of human resources. This research aims to describe the urgency of digitizing learning for Madrasah Aliyah Islamic Boarding School students in the Society 5.0 era. This research uses a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and a literature study. The research results show the importance of digitalization learning in the era of society 5.0 in Islamic boarding school-based Madrasah Aliyah, activists and stakeholders in education, get an overview of the application of technology learning, which is more specific to communication tools, the challenges of implementing digitalization learning, and the efforts that need to be made to maximize digitalization learning in Islamic boarding school-based Islamic schools.